Evaluation of Recombinant Viral Inhibitor Protein for Whiteleg Shrimp Resistance Against White Spot Syndrome Virus - Afif Abdurrahman; Alimuddin Alimuddin; Agus Oman Sudrajat; Sri Nuryati (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Viral inhibitor protein (VIP) contributes to shrimp resistance against virus infection. VIP can be used as a new strategy to control white spot syndrome virus (WSSV) infection in shrimp culture by inhibiting its action. This study aimed to evaluate the application of VIP on the whiteleg shrimp (Litopenaeus vannamei) to inhibit the WSSV infection. Shrimp at an average body weight of 6.66±0.08 g was injected by recombinant VIP with two different concentrations (1 μg/g and 10 μg/g) and challenged with WSSV. As a positive control was the shrimp not injected with recombinant VIP and challenged with WSSV, and as a negative control was the shrimp not injected with recombinant VIP and not challenged with WSSV. The results showed that the survival rate of shrimp that were injected with recombinant VIP was significantly increased after being challenged with WSSV (P<0.05). The survival and immune response of shrimp that were injected with recombinant VIP were higher than the positive controls (P<0.05). In this study, the application of recombinant VIP can significantly increase the shrimp resistance against WSSV up to 95.65% higher than the positive control.